Exploring new structural features of the 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino]benzenesulphonamide scaffold for the inhibition of human carbonic anhydrases - Simona Distinto; Rita Meleddu; Francesco Ortuso; Filippo Cottiglia; Serenella Deplano; Lisa Sequeira; Claudia Melis; Benedetta Fois; Andrea Angeli; Clemente Capasso; Rossella Angius; Stefano Alcaro; et al. (Taylor & Francis Group, 2019)
A library of 4-[(3-methyl-4-aryl-2,3-dihydro-1,3-thiazol-2-ylidene)amino]benzene-1-sulphonamides (EMAC8002a-m) was designed and synthesised to evaluate the effect of substituents in the positions 3 and 4 of the dihydrothiazole ring on the inhibitory potency and selectivity toward human carbonic anhydrase isoforms I, II, IX, and XII. Most of the new compounds preferentially inhibit the isoforms II and XII. Both electronic and steric features on the aryl substituent in the position 4 of the dihydrothiazole ring concur to determine the overall biological activity of these new derivatives.